Enhanced esterification process of 5-hydroxyeicosatetraenoic acid (5-HETE) in PMN from asthmatic patients - Radeau, T.; Godard, P.; Chavis, C.; Crastes de Paulet, A.; Damon, M. (Prostaglandins, 1992)
Polymorphonuclear neutrophils (PMN) generate 5-HETE which can be retained within cells as free metabolites or esterified into cellular lipids. Since this metabolite has been shown to have certain inflammatory porperties, we compared the generation and distribution profile of 5-HETE in A 23187-stimulated PMN from asthmatic patients (AP) and normal subjects (NS). 5-HETE was analyzed using RP-HPLC. After 5 min , total 5 HETE generation was similar in the two populations. However, esterified 5-HETE was significantly enhanced in AP (72 ± 3 % versus 47 ± 2 % of the total synthesis, p < 0.005), whereas intracellular free 5-HETE was decreased (13 ± 3 % versus 37 ± 4 %, p < 0.005) and similar low release was observed. Kinetic studies showed that PMN from AP esterified 5-HETE more rapidly and to a greater extent than PMN from NS. By contrast, more intracellular free 5-HETE was recovered in PMN from NS. Esterification seems to be the major pathway of 5-HETE metabolism in PMN from AP. Moreover, we showed that most of the 5-HETE added exogenously was esterified into cellular lipids. In these experimental conditions, PAF-induced migration of PMN was increased. The enhanced ability of PMN to migrate could be due to the increase of 5-HETE esterification process.